2018
DOI: 10.1016/j.nicl.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant oscillatory dynamics during somatosensory processing in HIV-infected adults

Abstract: While the arrival of combination antiretroviral therapy significantly decreased the prevalence of HIV-associated dementia, between 35 and 70% of all infected adults continue to develop some form of cognitive impairment. These deficits appears to affect multiple neural subsystems, but the mechanisms and extent of damage are not fully understood. In the current study, we utilized magnetoencephalography (MEG), advanced oscillatory analysis methods, and a paired-pulse somatosensory stimulation paradigm to interrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 62 publications
4
39
0
Order By: Relevance
“…For each comparison, at least 10,000 permutations were computed to build a distribution of cluster values. Further details of this method and our processing pipeline can be found in recent papers Spooner et al 2018aSpooner et al ,b, 2020McDermott et al 2019).…”
Section: Meg Preprocessing Time-frequency Transformation and Sensor-mentioning
confidence: 99%
“…For each comparison, at least 10,000 permutations were computed to build a distribution of cluster values. Further details of this method and our processing pipeline can be found in recent papers Spooner et al 2018aSpooner et al ,b, 2020McDermott et al 2019).…”
Section: Meg Preprocessing Time-frequency Transformation and Sensor-mentioning
confidence: 99%
“…In line with the most recent studies of somatosensory gating, we evaluated the effect of ISI on the dynamics of high-frequency gamma (>30 Hz) oscillations in response to the first and second stimulation ( Cheng et al, 2016b ; Kurz et al, 2017 ; Spooner et al, 2018 , 2019 ; Wiesman et al, 2017 ). Critically, we found that the gating of somatosensory input was optimal (i.e., smaller gating ratios) when stimulations were presented 200 ms apart from one another, irrespective of whether this ratio was calculated using peak oscillatory power or peak frequency.…”
Section: Discussionmentioning
confidence: 99%
“…This weakened response to stimuli presented in rapid succession is thought to reflect the brain’s capacity to filter irrelevant information to preserve neural resources for more behaviorally relevant stimuli ( Adler et al, 1982 , 1998 ; Cromwell et al, 2008 ; Nagamoto et al, 1989 , 1991 ; Venables, 1964 ). SG has been examined in many clinical populations and across multiple sensory modalities (e.g., auditory and somatosensory) and broadly is known to be aberrant in aging, as well as many psychiatric and neurological conditions (e.g., schizophrenia, bipolar disorder, cerebral palsy, neuroHIV ( Brinkman and Stauder, 2007 ; Cheng et al, 2015a ; Cheng et al, 2016a ; Cheng et al, 2015b ; Cheng and Lin, 2013 ; Kisley et al, 2003 ; Kurz et al, 2017 ; Light and Braff, 1999 ; Spooner et al, 2018 ; Spooner et al, 2019 ; Thoma et al, 2017 )). Historically, SG paradigms have used a paired-stimulus presentation design, whereby pairs of auditory tones or electrical stimulations are administered in close temporal proximity to evaluate gating in the auditory or somatosensory domain, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations